THE IMPLEMENTATION OF BLOCKCHAIN IN INTERNATIONAL TRADE - Galang Firman Maulana; Agung Juliarto (Diponegoro Journal of Accounting, 2021)
The logistics in international trade is become more complex because it involved many parties in the process. The complexity creates some challenges that cannot be resolve by traditional international trade system. A lot of paperwork, inefficiencies and tracking become the problems of international trade. Blockchain is a technology which has great potential to resolve all those problems. This research is aimed to answer the research problem: “is blockchain technology a solution for international shipping?” by providing the reader about potential and challenges for implementing blockchain in international trade. After conducting this research, the researcher finds that blockchain can be a good solution for international trade, if the company can overcome the challenges. The researcher also found that blockchain implementation is not easy, there are many challenges that has to be faced for a company, for example, lack of knowledge and ensuring integration of third application used for blockchain and many more. However, if a company can overcome those challenges, the company will be received great advantages by implementing blockchain.